Homosexuality in Hetero-sexist and Collectivist Context: From the Experience of Homophobia and the Anxiety of Socio-cultural Rejection to Identity Strategies - Yannick, Tamo Fogué; Alex Djibril, Tsagho Tchimeji (European Scientific Journal, ESJ, 2023)
This study raises the problem of failures in the construction of identity strategies among homosexuals in a homophobic and collectivist cultural context. It is guided by the models of identity strategies of Bajoit (2000) and Mellini (2009), and aims to understand their mechanisms of socio-cultural adaptation. Through the Interpretative Phenomenological Approach (API), we analyzed the speeches of two 24-year-olds and one 25-year-old, from Bamileke culture, encountered in a care structure for PLHIV and LGBTI at the West-Cameroon. Uninfected, they totaled scores of 10 to 11 on the Kinsey homosexual orientation scale translated by Tsagho (2014), and self-identify as homosexuals with genito-anal investment. It shows that they internalize a potentially vulnerable hetero-normative cultural signifier, due to their socialization in a culture that claims to be vitalist and whose cohesion and durability through procreation take precedence over personal aspirations/orientations. What reveals in their experience, a strong valence of anxiety of socio-cultural rejection. To manage these anxiety-provoking effects, they implement identity strategies such as hiding, denial, repair and avoidance. Indeed, because of the culturally hetero-sexist denial pact to which they have unconsciously subscribed, they camouflage themselves mainly in facade heterosexual unions, where they conceal their homosexual relations/relationships on the basis of friendship, without being discovered. What keeps them safe from suicide, abundantly noted in the literature (Firdion & Verdier, 2007) on psychiatric epidemiology in homosexuals.